Education Revolution: Leveraging Technology to Improve Learning Quality by 2025 - Saputra, Moch Panji Agung; Suhaimi, Nurnisaa binti Abdullah; Wahid, Alim Jaizul (Research Collaboration Community (RCC), 2025)
The technological transformation in education in 2025 has had a significant impact on the way we teach and learn. The use of artificial intelligence (AI) and learning analytics enables a more personalized, interactive, and adaptive learning experience. AI helps provide rapid feedback and adapts learning materials to students’ needs, while learning analytics enables real-time monitoring of student progress. Despite the many benefits that can be gained, the main challenges faced are the digital divide between urban and rural areas, limited infrastructure, and issues of training for educators and protection of students’ personal data. Therefore, investment in infrastructure, training for educators, and development of data protection policies are crucial to ensure effective implementation of technology in education. Technology can play a major role in creating a more inclusive and adaptive education, provided that the existing challenges can be overcome.